Comparing the Diagnostic Performance of Micro- Ultrasound-Guided Biopsy Versus Multiparametric Magnetic Resonance Imaging-Targeted Biopsy in the Detection of Clinically Significant Prostate Cancer: A Systematic Review and Meta-Analysis - Finín Cotter; Sachin Perera; Niranjan Sathianathen; Nathan Lawrentschuk; Declan Murphy; Damien Bolton (Société Internationale d’Urologie Journal)
BackgroundMicro-ultrasound is a novel, high-resolution imaging modality that aims to improve the accuracy of prostate cancer diagnosis compared with TRUS-guided biopsy. While traditional ultrasound systems operate at 8 to 12 MHz, micro-ultrasound operates at 29 MHz, allowing enhanced recognition of microstructures with 300% higher resolution. Micro-ultrasound can potentially identify and target in real-time suspicious lesions, improving sensitivity and the negative predictive value for clinically significant prostate cancer. It may be a low-cost alternative to multiparametric magnetic resonance imaging (mpMRI) in the detection of prostate cancer. MethodsA systematic review and meta-analysis was performed comparing the diagnostic performance of micro-ultrasound-guided prostate biopsies with mpMRI-targeted prostate biopsies in the detection of clinically significant prostate cancer. PubMed, EMBASE, SCOPUS, and Cochrane CENTRAL databases were searched to identify relevant studies published up to July 2022. ResultsA total of 15 studies were included for the systematic review, with 12 of those studies being included for the meta-analysis. The pooled sensitivity and specificity for micro-ultrasound-guided biopsies detecting clinically significant prostate cancer were 89% (95% CI 83 to 93) and 31% (95% CI 23 to 40) respectively (I2 = 0%). In comparison, the pooled sensitivity and specificity for mpMRI-targeted biopsies detecting clinically significant prostate cancer were 86% (95% CI 73 to 93) and 32% (95% CI 18 to 50) respectively (I2 = 16%). There was no statistically significant difference in the sensitivity or specificity between micro-ultrasound and mpMRI. Subgroup analysis found no difference in MRI subgroups based on blinding (P = 0. 383). ConclusionMicro-ultrasound-guided biopsies are comparable to mpMRI targeted biopsies with no difference in the detection of clinically significant prostate cancer between the 2 modalities. Large, multicentre, prospective studies are required to further substantiate the use of micro-ultrasound as an alternative to or in conjunction with mpMRI in the detection of prostate cancer.